Influence of culture on social representation of wines produced by various methods: Natural, organic and conventional. (January 2021) - Urdapilleta, Isabel; Demarchi, Samuel; Parr, Wendy V.
Highlights: We investigated social representation of organic, natural and conventional wines. We employed the concept of Distance to the Object to ascertain influence of culture and expertise on wine representations. Stability of social representations was highest for organic wines. Social representations were more consensual amongst French participants than New Zealand participants. The content of wine descriptions differed as a function of wine type, culture, and expertise. Abstract: The overall aim of the present study was to investigate the social representation of wines produced by various methods of wine production, in particular in relation to the concept of Distance to the Object (DO). The DO concept postulates that some participants will have a greater knowledge of the object (wine), feel more involved with it, and develop more practices related to wine, than other participants. We compared the social representations of French and New Zealanders of two levels of domain specific expertise (wine professionals; wine consumers) concerning three wine types, natural wine, organic wine, and conventionally-produced wine. Via a preliminary study, we validated our DO questionnaire. In the main analysis, results demonstrated French participants to have a higher level of involvement in wine than New Zealanders, and professionals to have higher levels on involvement, personal identification and capacity for action than consumers. New Zealanders expressed more knowledge and levels of practices than the French, and professionals more than consumers did. Results also showed that organic wine produced the most structured representations (i.e., participants more often quoted the same words) followed by natural wines, with conventional-wine representation the least structured. French participants' representations were more structured than New Zealanders, and consumers' representations more structured than those of professionals. Finally, by drawing on data concerning the frequencies, rank and valence of the words evoked by participants, we demonstrated differences in the content of participants' social representations as a function of wine-production method, culture, and level of domain-specific expertise, demonstrating how these variables influence wine representation.